2020
DOI: 10.21203/rs.2.15813/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Asymptomatic Bacteriuria and Sterile Pyuria among Antenatal Attendants in hospitals in Northern Ghana

Abstract: Background Asymptomatic bacteriuria (ASB) and sterile pyuria (SP) are complexities of UTI whose prevalence are not known in the northern sector of Ghana. Our aim was to determine the occurrence of sterile pyuria and asymptomatic bacteriuria among pregnant women accessing antenatal care at a secondary and tertiary care hospitals in Tamale, northern Ghana.Methods A cross sectional study was conducted by screening 530 pregnant women with no signs of acute urinary tract infection attending antenatal clinic for a p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The ASB proportion in the present study was lower compared to some earlier studies from sub-Saharan Africa, citing proportions of 7% − 40% (22)(23)(24)(25), but it was comparable to those found in other studies (26,27). The presently lower proportions of ASB may be related to the stringent de nition, i.e.…”
Section: Comparison With Other Studiessupporting
confidence: 54%
See 2 more Smart Citations
“…The ASB proportion in the present study was lower compared to some earlier studies from sub-Saharan Africa, citing proportions of 7% − 40% (22)(23)(24)(25), but it was comparable to those found in other studies (26,27). The presently lower proportions of ASB may be related to the stringent de nition, i.e.…”
Section: Comparison With Other Studiessupporting
confidence: 54%
“…The presently lower proportions of ASB may be related to the stringent de nition, i.e. including only Enterobacterales as signi cant organisms, whereas in most other studies with higher ASB proportions, Staphylococci represented a substantial number of cases (22)(23)(24)(25).…”
Section: Comparison With Other Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…The ASB proportion in the present study was lower compared to some earlier studies from sub-Saharan Africa, citing proportions of 7-40% [17,[22][23][24], but it was comparable to those reported elsewhere (range 1.9-9.5%) [25,26]. The presently lower proportions of ASB may be related to the stringent definition, i.e.…”
Section: Comparison With Other Studiessupporting
confidence: 49%
“…The current rate of gestational UTI prevalence in this region is much higher as compared to 27.6% reported in the general population among adults attending medical care in Kiambu level 5 hospital (15), and 21.5% among pregnant women attending ANC in Nairobi, Kenya (16). Other similar hospital-based studies in Sub-Saharan Africa have shown varying prevalence rates of gestational UTI infections; 3.7% Mbale, Uganda (35), 35% in Mbarara Uganda (36), 15.7 % in Ethiopia (28) and 20% and 35.5% in Tamale Central and Tamale Teaching hospitals in Ghana (37) and 18.8% in Sri Lanka, following urine culture and biochemical analysis during investigations. A systematic review of studies on the prevalence of gestational uro-pathogens and their antimicrobial resistance patterns in developing countries in Asia and Africa reported an overall rate of 13.5%.…”
Section: Discussionmentioning
confidence: 93%